Economic law in globalizing markets - Meessen, Karl Matthias (The Hague : Kluwer Law International ; Frederick, MD : sold and distributed in North, Central and South America by Aspen Publishers, 2004)
This study takes note of a new and additional function of economic law. Part I sets out to examine the making of economic law by states, by business and by international and supranational organizations. Part II discusses some of the main rules of substantive economic law divided into chapters on market law, transactions law and property rights law, and Part III addresses key issues of enforcement by the executive branch, on the one hand, and by the judiciary and arbitral tribunals, on the other.
Includes bibliographical references (p. 347-374) and index.
oif 02/03/15
Loan
Keywords: Industrial laws and legislation; Commercial law; Right of property; Investments, Foreign (International law); Globalization